Selection towards larger body size in both herbivorous and carnivorous synapsids during the Carboniferous - Neil Brocklehurst; Kirstin S. Brink (Canadian Science Publishing, 2017)
Body size is one of the most important characteristics of an organism, impacting a great variety of ecological characteristics. The influence of diet on body size has received considerable attention, with previous studies suggesting a greater tendency towards increased body size in herbivores than macro-carnivores. The earliest known herbivorous and macro-carnivorous synapsids provide an ideal case study for examining body size evolution in different dietary regimes. Sphenacomorpha contains two lineages: Edaphosauridae (some of the most abundant terrestrial herbivores in the late Carboniferous and early Permian), and Sphenacodontia (the largest and most abundant carnivores of that time). Phylogenetic comparative analyses are used to compare trait evolution in sphenacomorphs, including a Bayesian method for identifying branches along which phenotypic selection occurred. Two branches show rapid increases in body size in the late Carboniferous. The first occurred in Edaphosauridae, along the branch leading to the herbivorous members. The later shift towards larger size occurred in Sphenacodontia, producing a clade of large carnivores. It is possible that the rapid appearance of large herbivorous synapsids in the Carboniferous provided the selective pressure for carnivores to increase their size. Following these two shifts, rates of evolution in edaphosaurids slowed significantly, but the carnivorous sphenacodontians showed further increases.